Morphometric and histochemical study of the human vocal muscle - Guida, Heraldo Lorena [UNESP]; Zorzetto, N. L. (Annals Publ Co, 2000)
The present study was conducted on vocal muscles removed at autopsy Rom adult individuals (10 men and 8 women, aes ranging from 48 to 78 years) with no laryngeal disease. Histologic analysis was performed with hematoxylin and eosin staining, and histochemical analysis was performed by nicotinamide-adenine-dinucleotide tetrazolium reductase, succinate dehydrogenase, and acid and alkaline myofibrillar adenosine triphosphatase reactions. The histochemical reactions showed that the muscle consists of slow-twitch oxidative (SO), fast-twitch glycolytic (FG), and fast-twitch glycolytic oxidative (FOG) fibers distributed in mosaic form. The frequencies of SO, FOG, and FG fibers were 40.50%, 54.75%, and 4.75%, respectively. The higher frequency of SO and FOG oxidative fibers characterizes the muscle as having aerobic metabolism, resistance to fatigue, and fast contraction. The mean minimum diameters were 31.37 mu m for SO fibers and 36.46 mu m for FOG and FG fibers.
Keywords: human; larynx; morphology; vocal muscle